Do Free Trade Agreements Increase Australian Trade: An Application of Poisson Pseudo Maximum Likelihood Estimator?. Issue 1 (2nd January 2020) - Timsina, Krishna P.; Culas, Richard J.
Abstract: This article examines the effects of Australia's free trade agreements on trade creation and export diversion of the total as well as sectoral trade. The empirical analysis implemented through Poisson pseudo maximum likelihood estimator with time and country-specific effects. Results showed the standard gravity variables are highly significant with the expected signs. Overall, the trade creation effects were greater than intra-block export diversion effects of FTAs on Australia's total trade. The trade creation effects of FTAs on the agricultural sector seems higher than the nonagricultural sector in Australia after deducting intra-block export diversion effects in the respective sectors.